Структурний аналіз надійності гідросистем сільськогосподарської техніки при використанні біологічних робочих рідин - Журавель, Дмитро Павлович; Zhuravel, Dmytro (Запоріжжя : 2024, 2024)
UA: В роботі обґрунтовано модель надійності, що дозволяє за статистичними характеристиками напрацювання на відмову їх елементів отримувати нормовані в технічних умовах усереднені значення часу на виконання технологічних операцій з технічного обслуговування та ремонту гідравлічних систем сільськогосподарської техніки за допомогою коефіцієнтів готовності Kг та технічного використання Kт.в. В результаті проведених досліджень встановлено, що коефіцієнт готовності для гідравлічної системи: на мінеральній оливі – 0,816; на біоливі – 0,791; на сумішевій оливі з покращеними показниками – 0,864, а коефіцієнт технічного використання: на мінеральній оливі – 0,632; на біоливі – 0,583; на сумішевій оливі з покращеними показниками – 0,728. Таким чином використання сумішевих робочих рідин з покращеними показниками дозволить підвищити показники коефіцієнтів готовності і технічного використання. EN: The work substantiates the reliability model, which allows, based on the statistical characteristics of the working time to failure of their elements, to obtain the averaged values of the time for performing technological operations for technical maintenance and repair of hydraulic systems of agricultural machinery, standardized in technical conditions, with the help of coefficients of readiness and technical use. As a result of the conducted studies, it was established that the coefficient of readiness for the hydraulic system: on mineral oil - 0.816; on bio-oil – 0.791; on mixed oil with improved indicators - 0.864, and the coefficient of technical use: on mineral oil - 0.632; on bio-oil – 0.583; on mixed oil with improved indicators - 0.728. Therefore, the use of mixed working fluids with improved indicators made it possible to increase the indicators of the coefficients of readiness and technical use. Thus, using the obtained dependencies, it is possible to reliably assess the degree of influence of different types of working fluids on the reliability of the hydraulic system of agricultural machinery, using generalized indicators, namely the coefficients of readiness and technical use. It is obvious that one of the ways to increase the readiness factor and technical use of agricultural machinery when using biological lubricating materials is the use of multifunctional additives and additives, which will eliminate the harmful effect of free fatty acids of oil on the metals of the coupling parts and ensure standardized resources of nodes and aggregates of agricultural machinery. Considering the hydraulic systems of agricultural machinery as complex technical systems prone to various types of failures, we proposed a reliability model that allows, based on the statistical characteristics of the working time to failure of their elements, to obtain the average values of the time for performing technical maintenance and repair operations standardized in technical conditions GS. The renewability of raw materials and relative cheapness compared to biodegradable, ecologically safe synthetic products determine the expediency of work on the solidification of working fluids of biological origin in the operation of agricultural machinery.
Structural analysis of the reliability of hydraulic systems of agricultural equipment using biological working fluids
Keywords: біоолива; моделювання надійності; гідравлічна система; сільськогосподарська техніка; коефіцієнт готовності; відмова; коефіцієнт технічного використання; bio-oil; reliability modeling; hydraulic system; agricultural machinery; readiness factor; failure; technical utilization factor